2018
DOI: 10.1590/1806-9061-2017-0666
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fucoxanthin Dietary Inclusion on the Growth Performance, Antioxidant Metabolism and Meat Quality of Broilers

Abstract: Fucoxanthin is a major carotenoid found in marine brown algae. This study investigated the impact of fucoxanthin on the growth performance, antioxidant metabolism and meat quality of broilers. Overall, 180 one-day-old male broiler chicks (Ross 308) were assigned to one control group (CONT) and 2 treatment groups (FUCO1 and FUCO2), with six replicates of 10 birds each. The CONT, FUCO1 and FUCO2 birds were fed a basal diet supplemented with 0, 100 and 200 mg/kg of fucoxanthin, respectively. Average body weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Sasaki et al (2010) [162] demonstrated feeding fucoxanthin to the broiler chicken enhanced both the plasma antioxidative status and meat color of the chicken. Moreover, fucoxanthin also decreased the number of harmful microorganisms and regulated the antioxidant metabolism of the chicken meat [163]. The addition of 10-15% of brown macroalgae into the basal diet of laying hens augmented the carotenoid content of the yolks by 7.5-10-fold [164].…”
Section: Commercial Products and Potential Applications Of Fucoxanthinmentioning
confidence: 98%
“…Sasaki et al (2010) [162] demonstrated feeding fucoxanthin to the broiler chicken enhanced both the plasma antioxidative status and meat color of the chicken. Moreover, fucoxanthin also decreased the number of harmful microorganisms and regulated the antioxidant metabolism of the chicken meat [163]. The addition of 10-15% of brown macroalgae into the basal diet of laying hens augmented the carotenoid content of the yolks by 7.5-10-fold [164].…”
Section: Commercial Products and Potential Applications Of Fucoxanthinmentioning
confidence: 98%
“…Seaweed contained numerous unique bioactive substances such as alginate, ulvan, laminarin, fucoidan, and fucoxanthin. Those compounds could inhibit the colonization of pathogenic bacteria (Escherichia coli and Salmonella Enteritidis), promote the growth of beneficial gut microbes (lactic acid bacteria), improve small intestinal architecture, antioxidant status, and immune response [39][40][41][42][43] . Together, those mechanisms could ultimately improve the growth performance of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…For example, food supplements with FU intended to contribute to the loss of weight and improve eye, brain, liver, and joint health, are being sold with the commercial name of ThinOgen ® and Fucovital ® . These products can be found in the form of oils or microencapsulated powders [ 93 ]. Furthermore, FU is being studied to help combat cancer-related diseases, showing different anticancer mechanisms of action, such as inhibition of cell proliferation, induction of apoptosis, cell cycle arrest, an increase of intracellular reactive oxygen species, and anti-angiogenic effects [ 84 , 88 , 94 , 95 , 96 , 97 ].…”
Section: Main Xanthophylls Present In Algaementioning
confidence: 99%